Bridging 'what I said' and 'why I said it': the role of metapragmatic awareness in L2 request performance. Issue 3 (3rd July 2017) - Li, Citing; Gao, Xuesong (Andy)
ABSTRACT: This article reports on a study that investigated the role of metapragmatic awareness of L2 learners in Hong Kong, and the impact it has on language choices when addressing requests in English. Simulated open role-plays and retrospective interviews were used to explore the ways in which mainland Chinese undergraduates assess, plan and produce their utterances. The results show that participants' self-monitoring of pragmalinguistic and sociopragmatic knowledge may contribute to metapragmatic awareness; their oral performance in target language pragmatics depends on these two types of knowledge, as well as on self-evaluation of mediating factors such as cognitive task demand and learner subjectivity. By bridging the gap between what learners say and why they say it, this article demonstrates how metapragmatic awareness mediates the process of real-time L2 pragmatic performance and how it emerges from such a mediated process.